Tuberous sclerosis: a survey in the canton of Vaud, Switzerland - Hagon-Nicod, Olivia; Fellmann, Florence; Novy, Jan; Lebon, Sébastien; Wider, Christian; Lazor, Romain; Bonny, Olivier (Frontiers in Medicine, 2024)
Aim of the studyTuberous sclerosis complex (TSC) is a genetic and multisystemic disorder that affects between 1/6’000 and 1/10’000 of newborns. Clinical criteria and/or genetic analysis establish the diagnosis. The mechanistic target of rapamycin (mTOR) inhibitors everolimus or sirolimus reduce the severity of several TSC-related clinical traits. We report here on the epidemiology and management of TSC patients in a large Swiss canton: the canton of Vaud.MethodWe extracted patient files containing the diagnostic code TSC in 2015 at the Lausanne University hospital (tertiary reference center for a population of about 755’000 people) and in specialized neurological institutions of the same region.ResultsWe identified 52 patients with a diagnosis of TSC. The majority of the patients with a pathologic result in genetic testing were positive for a pathogenic variant in the TSC2 gene, including five cases of contiguous gene deletion syndrome of TSC2 and PKD1 causing both polycystic kidney disease and TSC. The most frequent clinical manifestations encountered were affecting the skin (87% of patients), the brain (83%), the heart (46%) and the kidneys (46%). Neuropsychiatric disorders were described in 56% of cases. At the time of data collection (2015), there were 2 patients using systemic mTOR inhibitors and 16 patients using topical mTOR inhibitors for dermatological features. Next, we compared this data with those of large published cohorts. While we found fewer cases than expected for the screened population, demographic as well as genetic data were overall similar to the literature. However, we observed that some clinical manifestations (renal, lung and neuropsychiatric disorders) were less frequently described in our cohort.ConclusionThis work indicates that TSC and some of its clinical manifestations is under-reported. It raises concern that patients with mild manifestations are often not referred to reference centers with dedicated multidisciplinary group. The follow-up by expert board is instrumental in offering systematic screening of all putatively affected organs and to assess the eligibility for targeted treatment.